Fluorescence Colour Control in Perylene‐Labeled Polymer Chains Trapped by Nanotextured Silicon. (26th January 2022) - Takao, Ryota; Ushiro, Kenta; Kusano, Hazuki; Yuyama, Ken‐ichi; Shoji, Tatsuya; Linklater, Denver P.; Ivanova, Elena; Juodkazis, Saulius; Tsuboi, Yasuyuki
Abstract: The ability to modulate, tune, and control fluorescence colour has attracted much attention in photonics‐related research fields. Thus far, it has been impossible to achieve fluorescence colour control (FCC) for material with a fixed structure, size, surrounding medium, and concentration. Here, we propose a novel approach to FCC using optical tweezers. We demonstrate an optical trapping technique using nanotextured Si (black‐Si) that can efficiently trap polymer chains. By increasing the laser intensity, the local concentration of perylene‐labelled water‐soluble polymer chains increased inside the trapping potential. Accordingly, the excimer fluorescence of perylene increased while the monomer fluorescence decreased, evidenced by a fluorescence colour change from blue to orange. Using nanostructure‐assisted optical tweezing, we demonstrate control of the relative intensity ratio of fluorescence of the two fluorophores, thus showing remote and reversible FCC of the polymer assembly. Abstract : An optical tweezer technique using nanotextured Si (black‐Si) can efficiently trap polymer chains. By increasing the laser intensity, the local concentration of perylene‐labelled water‐soluble polymer chains increased inside the trapping potential. Accordingly, the excimer fluorescence of perylene increased while the monomer fluorescence decreased. Based on the behaviour, we can control the fluorescence colour; blue, green, yellow‐green, yellow, and orange.